Factors Associated with the Uptake of Maternal Services among Pregnant Mothers in Malava Sub-County, in Kakamega County, Kenya - Bwana, Mong’ina Lydiah (JOOUST, 2023)
Over the past decade, Kenya has made tremendous efforts to enhance maternal and child health. Maternal health policies such as maternal care have enhanced maternal and child health in all public health facilities. Despite these attempts, public health facilities for maternal and child health are still underused. This study employed a descriptive cross-sectional design to investigate the factors associated with the use of maternal health services, by assessing the individual and health system factors that influence the health-seeking behavior regarding maternal health among 301 pregnant mothers in Malava Sub-County, Kakamega County. This descriptive cross- sectional study used both quantitative and qualitative approaches, where questionnaires were administered to purposively selected pregnant women for the study, while 12 healthcare workers were interviewed. Quantitative data was analyzed using descriptive inferential statistics (Pearson correlation and multiple regression analysis to assess the association between the variables of socio-economic and health facilities and the uptake of maternal health services; p<0.05), using SPSS v.23, while qualitative data was subjected to thematic analysis. Results were presented as frequency, percentage and coefficients, and displayed on tables. The uptake of maternal health service was influenced by the cultural and religious beliefs of the women. In addition, 53.8% and 77.7% of the women could not optimally attend antenatal and post-natal care clinics, respectively, because government health facilities were located far away from their homes, and they also had limited information about maternal health care. This study recommends that to improve access to maternal health care, the Ministry of Health (County Government of Kakamega) devices approaches for ensuring that health services close and available to the community where people live. The Ministry should in addition exploit available media networks to sensitize the community on the need to use the available services. In addition, individual hospital management should increase the awareness of maternal health care services.
Keywords: Maternal Services; Pregnant Mothers